Integrasi Nilai Keislaman dalam Projek Penguatan Profil Pelajar Pancasila (P5RA) - Alfian Gunawan; Nur Aisyah Zulkifli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRAK The implementation of the Pancasila and Rahmatan lil 'Alamin Student Profile Strengthening Project (P5RA) in madrasas requires the systematic integration of Islamic values, but its implementation is still influenced by the readiness of teachers and the dynamics of students. This study aims to analyze the integration process in the planning, implementation, and evaluation of the project. Using a qualitative approach and Miles and Huberman's interactive analysis, data were collected through in-depth interviews with five teachers and five students, then analyzed through the stages of reduction, presentation, and verification. The results show that the values of trustworthiness, discipline, cooperation, manners, and social awareness are the most dominant values integrated through work meetings, module development, habituation, insertion of verses and hadiths, reflection, and teacher role modeling. Although student responses tended to be positive, the implementation of integration still faced obstacles in the form of the unpreparedness of some teachers, time constraints, and variability in student consistency. These findings imply the need to strengthen teacher competence and continue character building so that the integration of Islamic values in P5RA can be more optimal and sustainable.